Evaluasi Penataan Fasilitas Terminal Tipe C Untuk Meningkatkan Efisiensi Operasional (Studi Kasus Terminal Tipe C Semanggi) - Wiguna, I Wayan Yudi Martha; Elang Ramadhani Subagyo; A.A Bagus Oka Khrisna Surya (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2023)
Semanggi Type C Terminal is located in Pasar Kliwon District, Surakarta City, whichhas an area of 2,111 m² and serves 2 urban public transportation routes totaling 45 operating fleets. The facilities available at Semanggi Terminal in accordance with PM 40 of 2015 concerning Road Transport Passenger Service Standards are only 42% ofthe total facilities and lack of private vehicle parking capacity. This study aims toevaluate the needs of terminal facilities and provide layout proposals for both facilitylayout design to circulation and parking lot layout design. By using terminal inventorysurvey data and other supporting data which is then carried out optimizationanalysis, the existing condition of Semanggi Terminal facilities and the need for ideal private vehicle parking space are produced. The results of this study can provideresults in the form of recommendations for the area of Semanggi Terminal facilityneeds of 61.54 m², circulation proposals to reduce existing conflict points by 35% and 50%, and the arrangement of private vehicle parking lots that can be used as park and ride facilities from those that can initially accommodate 17 SRP to 21 SRP according to the Decree of the Director General of Land concerning TechnicalGuidelines for Parking Implementation.